Naval Diplomacy: Upaya Defensif Indonesia dalam Konflik Laut Tiongkok Selatan di Era Joko Widodo - Satwika Paramasatya; Wing Witjahyo Poespojoedho (Universitas Airlangga, 2019)
The conflict involving many countries in the South China Sea has notended nor subsided. Regional tension and claims between countries areincreasing and Indonesia participates in this round of conflict. As theworld’s largest archipelagic country and an ASEAN member country thatupholds peace, security and regional stability, Indonesia then has to playan active role in the conflict. In order to do so, Indonesia is using navaldiplomacy as a way to achieve effective conflict resolution within theregion. Regarding the phenomenon, this study used the concept of seapower and naval diplomacy to explain measures that have been taken bythe Indonesian government under Joko Widodo’s presidency in resolvingthe conflicts involving its territories in the South China Sea. The author’sanalysis showed that Indonesia’s policies of using naval diplomacy in theSouth China Sea conflict have a positive and effective outcome in achievingconflict resolution and peace condition that has been confined by longtermobstacles and challenges.